2015
DOI: 10.1371/journal.pone.0142448
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of CD68 Synovial Macrophages in Celastrol Treated Arthritic Rats

Abstract: BackgroundRheumatoid arthritis (RA) is a chronic immune-mediated inflammatory disease characterized by cellular infiltration into the joints, hyperproliferation of synovial cells and bone damage. Available treatments for RA only induce remission in around 30% of the patients, have important adverse effects and its use is limited by their high cost. Therefore, compounds that can control arthritis, with an acceptable safety profile and low production costs are still an unmet need. We have shown, in vitro, that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 64 publications
5
37
0
Order By: Relevance
“…5 Celastrol inhibited angiogenesis-mediated tumor growth and alleviated macrophage-mediated inflammation. 20,40 The results of the present study demonstrated that CNMs suppressed the expression of VEGF and MMP-9 in activated macrophages and corneal tissue, suggesting that CNMs might inhibit CNV by downregulation of the secretion activity of macrophages, which is consistent with the in vitro experimental result.…”
Section: Cnms Suppress Cnv Induced By Activated Macrophages In the Rasupporting
confidence: 90%
“…5 Celastrol inhibited angiogenesis-mediated tumor growth and alleviated macrophage-mediated inflammation. 20,40 The results of the present study demonstrated that CNMs suppressed the expression of VEGF and MMP-9 in activated macrophages and corneal tissue, suggesting that CNMs might inhibit CNV by downregulation of the secretion activity of macrophages, which is consistent with the in vitro experimental result.…”
Section: Cnms Suppress Cnv Induced By Activated Macrophages In the Rasupporting
confidence: 90%
“…Periploca forrestii shows several medicinal prophylactic effects in traditional Chinese folk medicine; because several plant saponins were recently found having therapeutic effects in different models of autoimmune diseases, such as arthritis [28, 29], we suggest that PFS may have clinically beneficial effects on autoimmune diseases by their induction of immunosuppression during chronic administration. Therefore, the present study was conducted to evaluate the anti-inflammatory and antiarthritic activities of PFS based on an experimental model of autoimmune arthritis (AIA model).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo , we observed that celastrol has anti-inflammatory effects both in an early and established phase of arthritis development, suppressing ankle swelling, joint inflammatory cell infiltration and proliferation, and serum IL-6 levels in AIA rats (39, 40). This inhibitory effect in cellular infiltration and proliferation may prevent and treat synovial pannus tissue development characteristic of RA patients and responsible for bone damage.…”
Section: Anti-inflammatory Properties Of Celastrolmentioning
confidence: 93%
“…Importantly, neither blood biochemical parameters nor tissue histological structures revealed drug-induced toxicity associated with the intraperitoneally administration of 1 mg/kg/day of celastrol for 18 days (40). …”
Section: Anti-inflammatory Properties Of Celastrolmentioning
confidence: 99%